Pengaruh kualitas konten instagram @shoesandcare terhadap minat beli followersnya - Prayogi, Anggit Estu; Saputro, Edy Purwo (Universitas Garut, 2026)
Abstract The background of this research is the decreasing interest in consumer purchases, so that in practice not all content produced is able to generate the expected response. This research aims to examine the extent to which the quality of Instagram content from @shoesandcare influences the purchase intention of its followers. This research uses a quantitative approach with an explanatory survey design to explain the relationship between content quality and purchase intention. The respondents in this research consisted of 97 students from the Communication Science Study Program at Universitas Muhammadiyah Surakarta who follow the Instagram account @shoesandcare. The respondents were selected using a purposive sampling technique based on specific criteria relevant to the objectives of the research. The research instrument used was a questionnaire with a Likert scale designed to measure respondents’ perceptions of Instagram content quality as well as their level of purchase intention. The measurement of the purchase intention variable in this research refers to the AIDA framework, which consists of attention, interest, desire, and action. The collected data were analyzed using simple linear regression to determine the influence of content quality on the purchase intention of followers. The results of the analysis indicate that there is a positive and significant influence between Instagram content quality and the purchase intention of @shoesandcare followers, with a significance value (p < 0.05). Furthermore, the coefficient of determination (R²) of 0.301 indicates that content quality explains 30.1% of the variation in consumers’ purchase intention, while the remaining 69.9% is influenced by other factors outside the research model. These findings suggest that the consistency and relevance of Instagram content management contribute to increasing followers’ tendency to make purchasing decisions. Keywords: Content quality; instagram; purchase intention; social media; AIDA. Abstrak Latar belakang penelitian ini adalah berkurangnya minat beli konsumen, sehingga pada praktiknya tidak semua konten yang diproduksi mampu menghasilkan respon yang diharapkan. Penelitian ini bertujuan untuk mengkaji sejauhmana kualitas konten Instagram @shoesandcare memengaruhi minat beli para pengikutnya. Penelitian ini menggunakan pendekatan kuantitatif dengan desain survei eksplanatif untuk menjelaskan hubungan antara variabel kualitas konten dan minat beli. Responden dalam penelitian ini berjumlah 97 orang yang merupakan mahasiswa Program Studi Ilmu Komunikasi Universitas Muhammadiyah Surakarta dan mengikuti akun Instagram @shoesandcare. Pemilihan responden dilakukan menggunakan teknik purposive sampling dengan mempertimbangkan kriteria tertentu yang relevan dengan tujuan penelitian. Instrumen penelitian yang digunakan berupa kuesioner dengan skala Likert yang dirancang untuk mengukur persepsi responden terhadap kualitas konten Instagram serta tingkat minat beli konsumen. Pengukuran variabel minat beli dalam penelitian ini mengacu pada kerangka AIDA yang terdiri dari attention, interest, desire, dan action. Data yang telah diperoleh kemudian dianalisis menggunakan metode regresi linear sederhana untuk mengetahui pengaruh kualitas konten terhadap minat beli followers. Hasil analisis menunjukkan bahwa terdapat pengaruh positif dan signifikan antara kualitas konten Instagram dan minat beli pengikut akun @shoesandcare dengan nilai signifikansi (p < 0,05). Selain itu, nilai koefisien determinasi (R²) sebesar 0,301 menunjukkan bahwa kualitas konten mampu menjelaskan sebesar 30,1% variasi minat beli konsumen, sedangkan sisanya sebesar 69,9% dipengaruhi oleh faktor lain di luar model penelitian. Temuan ini menunjukkan bahwa konsistensi serta relevansi pengelolaan konten Instagram berkontribusi dalam meningkatkan kecenderungan followers untuk melakukan pembelian. Kata-kata kunci: Kualitas konten; instagram; minat beli; media sosial; AIDA.